Preferences of Giant Gouramy (Osphronemus gouramy, Lac, 1801.), Walking Catfish (Clarias sp.) and Red Nile (Oreochromis sp.) on Natural Feed in Fish Culture - Dea Nafila; Rustadi Rustadi; Djumanto Djumanto (Universitas Gadjah Mada, 2018)
The aim of this study was to determine the preference for plankton as natural feed by giant gourami, walking catfish, and red nile on intensive aquaculture system. The study was designed using Completely Randomized Design (RAL), with two replications. Each fish was kept in six concrete tanks with dimension 2x2x1 m³ and 60 cm water level. Water source were from wells. Commercial pellet feed was given in three times daily ad libitum. Water samples were filtered and two individual fish were collected for plankton samples from pond water and alimentary canal, respectively, every two week, simultaneously with water quality measurements. Plankton samples were preserved using 5% formaldehyde and was observed under a compound light microscope with 100x magnification. The amount of plankton in the alimentary canal was converted to volume. Data were analyzed descriptively. The result showed that the volume contents proportion of plankton in the alimentary canal was less than 1%. The volume of plankton proportion in the alimentary canal of red nile were found the most than other fish. Each fish had the same preference of plankton of Lepocinclis and Scenedesmus, but different from other species of plankton. The plankton that utilized by giant gouramy were Crucigenia, Diadesmis and Navicula, whereas walking catfish was Pediastrum, and red nile was Microcystis. The plankton that preferred by giant gouramy were Crucigenia, Oscillatoria, Splirullina, and Synedra, walking catfish was Navicula, while red nile were Chrysamoeba and Tintinnidium.